Sport as a State Tool to Strengthen the Image of Franco’s Regime: Sport as a state tool to strengthen the image of Franco’s regime - Lopez Iglesias, Victorino (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
General Franco, from the moment he became head of state in the midst of the Spanish Civil War, developed mechanisms for legitimising and constructing his personal image and that of his political regime. Sport was one of his favourite tools to mobilise and unite a broken and fractured society that survived the post-war period and Spain`s international isolation in precarious conditions.